Jin’s three-needle acupuncture technique for chronic fatigue syndrome: a study protocol for a multicentre, randomized, controlled trial - Wenjia Lin; Xin-lin Chen; Qi Chen; Junmao Wen; Xinghua Chen (Trials, 2019)
Abstract Background With an unclear pathomechanism, no confirmed treatment regimen has been established for chronic fatigue syndrome (CFS). Acupuncture is applied as an alternative therapy for CFS. As a kind of acupuncture therapy, Jin’s three-needle acupuncture (JTN) has been applied to treat CFS. However, few large-sample randomised controlled trials on JTN treatment for CFS have been reported. We designed this study to evaluate the efficacy and safety of JTN treatment for CFS. Method/design This study is a multicentre, single-blind, randomised controlled trial. Patients who meet the inclusion criteria will be recruited and randomly assigned to either the JTN treatment group or the basic acupuncture group. Both interventions will be conducted for five consecutive days per week and last for 2 weeks. The primary outcome is the effective rate based on the 14-item Fatigue Scale (FS-14) score. Other outcome measures include the Fatigue Assessment Scale (FAI), the Depression Status Inventory (DSI), and the Self-rating Anxiety Scale (SAS). Plasma adrenocorticotropic hormone (ACTH), plasma cortisol, and serum levels of IL-2 and IFN-γ will also be measured in this study. Adverse events will be observed and recorded for the safety evaluation. Discussion This study may help to identify the efficacy and safety of JTN acupuncture treatment for CFS. Trial registration Chinese Clinical Trial Registry, ID: ChiCTR-IOR-17011009. Registered on 29 March 2017.